Applying native proteases from melon to hydrolyze kilka fish proteins (Clupeonella cultriventris caspia) compared to commercial enzyme Alcalase. (30th March 2019) - Alavi, Farhad; Jamshidian, Majid; Rezaei, Karamatollah
Highlights: Crude melon extract (CME) was investigated as a new source of enzyme compared to a commercial enzyme, Alcalase. Kilka protein hydrolysates (KPH) yielded high protein content and low fat. Functional properties of KPH were related to the degree of hydrolysis. Alcalase hydrolysis produced higher protein recovery and hydrolysis rate. The KFH made by CME showed better functional properties than those of Alcalase. Abstract: The enzymatic hydrolysis (at 2.5, 5.0, 10.0, and 15.0% degree of hydrolysis, DH) of kilka fish ( Clupeonella cultriventris caspia ) was investigated using a crude melon extract (CME) as well as a commercial serine protease (Alcalase). Hydrolysates from both enzymatic treatments were analyzed for their antioxidant and functional properties. The hydrolysis resulted in increased antioxidant activities of kilka fish protein hydrolysates and the highest antioxidant activity was obtained for the CME hydrolysates with 5.0% DH level. Both treatments improved the protein solubility level to >65% within a pH range of 2.0–10.0. At a given DH level, CME hydrolysates showed higher oil and water holding capacities than Alcalase hydrolysates. Hydrolysates from CME exhibited better emulsifying properties compared to those prepared by Alcalase, particularly at low DH (2.5 and 5.0%). According to the results of this study, CME can be suggested as a new source of proteolytic enzymes for fish protein hydrolysis.